Recent Progress on Chemical Production From Non-food Renewable Feedstocks Using Corynebacterium glutamicum - Zhang, Bin; Jiang, Yan; Li, Zhimin; Wang, Fei; Wu, Xiao-Yu (Frontiers in Bioengineering and Biotechnology, 2020)
Due to the non-renewable nature of fossil fuels, microbial fermentation is considered a sustainable approach for chemical production using glucose, xylose, menthol, and other complex carbon sources represented by lignocellulosic biomass. Among these, xylose, methanol, arabinose, glycerol, and other alternative feedstocks have been identified as superior non-food sustainable carbon substrates that can be effectively developed for microbe-based bioproduction. Corynebacterium glutamicum is a model gram-positive bacterium that has been extensively engineered to produce amino acids and other chemicals. Recently, in order to reduce production costs and avoid competition for human food, C. glutamicum has also been engineered to broaden its substrate spectrum. Strengthening endogenous metabolic pathways or assembling heterologous ones enables C. glutamicum to rapidly catabolize a multitude of carbon sources. This review summarizes recent progress in metabolic engineering of C. glutamicum toward a broad substrate spectrum and diverse chemical production. In particularly, utilization of lignocellulosic biomass-derived complex hybrid carbon source represents the futural direction for non-food renewable feedstocks was discussed.